2013
DOI: 10.1037/a0027162
|View full text |Cite
|
Sign up to set email alerts
|

Comparing incarcerated and college student women with histories of childhood sexual abuse: The roles of abuse severity, support, and substance use.

Abstract: Childhood sexual abuse (CSA) is often a risk factor for negative psychological and psychosocial outcomes. For example, some studies find that survivors of CSA are at an increased risk for experiencing involvement with the criminal justice system (e.g., incarceration). To examine the relationship between CSA and incarceration outcomes in women, data were obtained from 169 inmates and 420 college students, a number of whom were survivors of some form of CSA (66.0% and 35.5%, respectively). Results suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 64 publications
4
32
0
Order By: Relevance
“…Although some studies found an association between child abuse and later homelessness (e.g., Herman, Susser, Struening, & Link, 1997;Stein, Leslie, & Nyamathi, 2002) or incarceration (e.g., Asberg & Renk, 2013), others did not find a direct link between child abuse and future homelessness , however. Nonetheless, child sexual abuse (CSA) is linked to a variety of risky behaviors among women (see Senn, Carey, & Vanable, 2008, for a review), including homeless women's reports of having traded sex (Simons & Whitbeck, 1991) and having experienced sexual assault (Heslin, Robinson, Baker, & Gelberg, 2007), suggesting the importance of examining victimization experiences.…”
Section: Victimization Among Marginalized Womenmentioning
confidence: 89%
See 1 more Smart Citation
“…Although some studies found an association between child abuse and later homelessness (e.g., Herman, Susser, Struening, & Link, 1997;Stein, Leslie, & Nyamathi, 2002) or incarceration (e.g., Asberg & Renk, 2013), others did not find a direct link between child abuse and future homelessness , however. Nonetheless, child sexual abuse (CSA) is linked to a variety of risky behaviors among women (see Senn, Carey, & Vanable, 2008, for a review), including homeless women's reports of having traded sex (Simons & Whitbeck, 1991) and having experienced sexual assault (Heslin, Robinson, Baker, & Gelberg, 2007), suggesting the importance of examining victimization experiences.…”
Section: Victimization Among Marginalized Womenmentioning
confidence: 89%
“…Consistently, the majority of incarcerated women also are mothers (e.g., Asberg & Renk, 2013;Scott & Dennis, 2012;Wildeman, 2009), with these women being more likely (relative to men) to be homeless prior to incarceration (see Nickel, Garland, & Kane, 2009, for a review). Such circumstances, in addition to the negative impact of maternal incarceration on children's functioning (Cho, 2010;see DeHart & Altshuler, 2009, for a review; Nickel et al, 2009;Raeder, 2012), present additional challenges for women.…”
mentioning
confidence: 95%
“…Most experts agree that an accurate estimation is about 50% (Asberg & Renk, 2012;Gilfus, 2002;Heney & Kristiansen 1998;Marcus-Mendoza & Wright, 2003;McClellan, Farabee & Crouch, 1997;Zlotnick, 1997), compared to a rate in the general population of about 30% (Asberg & Renk, 2012;Heney & Kristiansen, 1998).…”
Section: Childhood Sexual Abusementioning
confidence: 99%
“…Incarcerated women are more likely to be involved with mental health services before incarceration and have more psychological problems than women in the community (Asberg & Renk, 2012;Bloom, Owen & Covington, 2004). Nationally, about 18% of the American population suffers from a mental illness (SAMSHA, 2014).…”
Section: Mental Illness In Incarcerated Womenmentioning
confidence: 99%
“…The picture for these parents is complex, however, as childhood maltreatment and trauma also are common, particularly for those parents who are involved with child welfare systems (15) and/or who have been incarcerated (e.g., (16,17)). In other words, childhood maltreatment experiences are related closely to substance misuse in adulthood (e.g., (18)).…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 99%